What are food systems and what can we know about their future? - Wiebe, Keith D.; Gotor, Elisabetta (International Food Policy Research Institute, 2025)
Food systems are made up of the people, resources, and activities involved in the production, processing, distribution, and consumption of food. We cannot know the future of food systems with certainty, but we can make informed projections about alternative possible futures and ways to achieve (or avoid) them. This book provides a mosaic of perspectives from a diverse group of experts on the state of knowledge about different aspects of the future of food systems and how they are interlinked. Pressure on land and water resources is projected to increase, extreme events will become more frequent, and healthy diets will remain out of reach for many, but innovation and improved policies and investments can help address these challenges. Synergies and trade-offs between these different challenges and goals mean that they need to be understood and addressed as integrated parts of dynamic food systems.